Pravno varstvo podatkovnih baz - Levovnik, Jure (Pravni letopis, 2014)
In the European Union, legal protection of investments in the creation of databases is based on one of the most curious institutions of intellectual property law, the so-called sui generis right which comes into existence if the creation of a database has resulted from a substantial investment and which, to certain extent and with certain limitations, prohibits third parties to take actions which could unreasonably prejudice the legitimate interests of the maker of the database related to such investment. The Directive 96/9/EC of the European Parliament and of the Council of 11 March 1996 on the legal protection of databases introduced this exclusive right with the aim to foster investments in the production of databases as advanced information storage and processing systems. This article discusses some of the fundamental aspects of legal protection based on the sui generis right, namely: legal definition of a database, conditions for the emergence and ownership of the sui generis right and substance and infringement of the sui generis right. As will be demonstrated, the regulation of the sui generis right is vague in several respects and leaves a lot of room for different interpretations.
Keywords: avtorske pravice; podatkovne baze; podatkovne zbirke; pravna ureditev; varstvo podatkov